Developmental regulation of SPO13, a gene required for separation of homologous chromosomes at meiosis I. - Wang, H T (1987)
Previous studies have demonstrated that the SPO13 gene is required for chromosome separation during meiosis I in Saccharomyces cerevisiae. In the presence of the spo13-1 nonsense mutation, MATa/MAT alpha diploid cells complete a number of events typical of meiosis I including premeiotic DNA synthesis, genetic recombination, and spindle formation. Disjunction of homologous chromosomes, however, fails to occur. Instead, cells proceed through a single meiosis II-like division and form two diploid spores. In this paper, we report the cloning of this essential meiotic gene and an analysis of its transcription during vegetative growth and sporulation. Disruptions of SPO13 in haploid and diploid cells show that it is dispensible for mitotic cell division. Diploids homozygous for the disruptions behave similarly to spo13-1 mutants; they sporulate at wild-type levels and produce two-spored asci. The DNA region complementing spo13-1 encodes two overlapping transcripts, which have the same 3' end but different 5' ends. The major transcript is 400 bases shorter than the larger, less abundant one. The shorter RNA is sufficient to complement the spo13-1 mutation. While both transcripts are undetectable or just barely detectable in vegetative cultures, they each undergo a greater than 70-fold induction early during sporulation, reaching a maximum level about the time of the first meiotic division. In synchronously sporulating populations, the transcripts nearly disappear before the completion of ascus formation. Nonsporulating cells homozygous for the mating-type locus show a small increase in abundance (less than 5% of the increase in sporulating cells) of both transcripts in sporulation medium. These results indicate that expression of the SPO13 gene is developmentally regulated and starvation alone, independent of the genotype at MAT, can trigger initial induction.